Infant and young child feeding practices among mother in Satar community - Ban, R K; Rajbanshi, L (Journal of Chitwan Medical College, 2017)
Infant and Young Child Feeding (IYCF) practices differ in communities due to differences in knowledge, culture and other socio-economic factors. The objective of this study was to find out the practices of Satar mothers on ICYF and their correlates. A descriptive study employing non-probability sampling technique was used to select 132 mothers who had infants aged from 6 months to 23 months. Descriptive statistics and chi-square test were used to find out the association between practice of breastfeeding and complementary feeding with selected socio demographic variables. Findings depicted that practice of breastfeeding was lower than complementary feeding among Satar mothers. About 37.1% respondents initiated breast feeding in less than an hour (≤ 1 hour). While 80.3% respondents fed colostrums, almost the half of them (43.4%) practiced prelacteal feeding. Exclusive breastfeeding and introduction of complementary foods at the age of six months were 49.2% and 51.5% respectively. Exclusive breast feeding was found to have significant association with educational level of respondents (p=<0.001), education level of her husband (p=<0.001), sex of children (p=0.023) and place of delivery (p=<0.001). Feeding practices in Satar community were found to be associated with mother’s educational status so there is still a need for programmes, which support and encourage breast-feeding particularly focusing more on younger and less well-educated mothers.